PENGARUH PENATAUSAHAAN ASET TETAP TERHADAP KUALITAS LAPORAN KEUANGAN PADA SKPD KOTA BANDUNG - Nabila Maulani; Rahma Nazila Muhammad (Jurnal Riset Akuntansi, 2025)
This study aims to determine the effect of fixed asset management on the quality of financial statements in the Regional Work Units (SKPD) of the Bandung City Government from 2019 to 2023. The research problem stems from the decline in the opinion of the Supreme Audit Agency (BPK) on the Local Government Financial Report (LKPD) of Bandung City from Unqualified Opinion (WTP) to Qualified Opinion (WDP) for two consecutive years, which was caused by weak fixed asset management such as administrative irregularities, and discrepancies between physical data and ownership documents. The research method used was a quantitative method with a descriptive approach. The research population included 63 Regional Work Units within the Bandung City Government, using a saturated sampling technique, so that the entire population was used as the sample. Primary data was obtained through questionnaires distributed to asset users and officials in charge of financial reporting, while secondary data was obtained from the Bandung City financial position reports for 2019–2023. Data analysis was performed using simple linear regression with the help of IBM SPSS software. The results showed that fixed asset management had a positive and significant effect on the quality of local government financial reports. The implications of this study emphasize that improving the accuracy of fixed asset recording, inventory, and reporting is necessary to make financial report presentation more reliable, relevant, and in accordance with Government Accounting Standards (SAP), thereby supporting an improvement in the BPK opinion to WTP in the future.